World Bank Group Impact Evaluations : Relevance and Effectiveness - Independent Evaluation Group (Washington, DC: World Bank, 2013)
The use of impact evaluations (IEs) to assess the causal impacts of development projects has expanded rapidly. Along with major innovations in statistical methods and econometrics, the recent impetus in IE has its roots in the debate about whether development programs achieve their objectives of reducing poverty and increasing economic growth. The renewed focus on results and the increasing calls for sound evidence on effectiveness have led to expectations that IE may help build the knowledge base of what does and does not work in development and where resources may be best allocated. Between 2004 and 2008, the number of Bank Group supported evaluations increased sevenfold. This increase is partly attributable to major IE initiatives at the World Bank, including the Development Impact Evaluation Initiative (DIME), the Africa Impact Evaluation Initiative, the Spanish Trust Fund for Impact Evaluation (SIEF), and efforts by the International Finance Corporation's (IFC) Advisory Services Results Measurement Unit (RMU). This sizable investment in IEs, together with the high expectations for them, contrasts with how little is known about whether the evaluations: (i) evaluate the primary objectives of Bank Group supported projects and help fill strategic, analytic, and policy knowledge gaps; (ii) are of high quality; and (iii) have influenced operational work (project design, implementation, and assessment), resource allocation, institutional strategy, policy making, or evaluation culture and capacity. In this report, the Independent Evaluation Group (IEG) assesses the extent to which experimental and quasi-experimental IEs supported by the World Bank Group have contributed to its development practices along several dimensions. The study aims to evaluate the relevance of both experimental and quasi-experimental IEs supported by the Bank Group in the past decade; their technical quality; their use and influence on the Bank Group's business lines and strategies and on client countries policies; and their contribution to building evaluation capacity. The objectives of the evaluation are similar to those of other recent IEG evaluations of analytical and advisory assistance (AAA) at the World Bank: the 2010 poverty and social impact analysis evaluation, the 2008 evaluation of economic and sector work and non-lending technical assistance, and other evaluations of particular AAA reports within country assistance reviews (IEG 2003, 2008, 2010).